2011
DOI: 10.1002/dta.250
|View full text |Cite
|
Sign up to set email alerts
|

The use of in vitro technologies and high‐resolution/accurate‐mass LC‐MS to screen for metabolites of ‘designer’ steroids in the equine

Abstract: Detection of androgenic-anabolic steroid abuse in equine sports requires knowledge of the drug's metabolism in order to target appropriate metabolites, especially where urine is the matrix of choice. Studying 'designer' steroid metabolism is problematic since it is difficult to obtain ethical approval for in vivo metabolism studies due to a lack of toxicological data. In this study, the equine in vitro metabolism of eight steroids available for purchase on the Internet is reported; including androsta-1,4,6-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…However, in the case of ATD, GC/MS was found to be not sensitive enough for the detection of both the in vitro and in vivo metabolites, most likely due to the extensive metabolism of ATD through the reductions of two ketone groups and three olefin groups. Liquid chromatography/high resolution mass spectrometry (LC/HRMS) has been proven to be useful and versatile for the identification and characterization of metabolites [13,[17][18]. The use of full-scan HRMS offers the advantage of the simultaneous detection of virtually an unlimited number of phase I metabolites, and also the direct detection of phase II metabolites such as glucuronide and sulfate conjugates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of ATD, GC/MS was found to be not sensitive enough for the detection of both the in vitro and in vivo metabolites, most likely due to the extensive metabolism of ATD through the reductions of two ketone groups and three olefin groups. Liquid chromatography/high resolution mass spectrometry (LC/HRMS) has been proven to be useful and versatile for the identification and characterization of metabolites [13,[17][18]. The use of full-scan HRMS offers the advantage of the simultaneous detection of virtually an unlimited number of phase I metabolites, and also the direct detection of phase II metabolites such as glucuronide and sulfate conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…In May 2014, aromatase inhibitors have been listed as one of the classes of hormone and metabolic modulators (Article 6E of the International Agreement of Breeding, Racing, and Wagering) which are prohibited to be administered to racehorses at any time in their career [11]. The metabolism of ATD has been reported in human [10,12], and the in vitro metabolic study of ATD in horses has been reported [13], but little is known about its biotransformation and elimination in horses. This paper describes the investigation of the in vitro and in vivo metabolism of ATD in horses with an objective to identify the most appropriate targets for detecting ATD administration.…”
Section: Introductionmentioning
confidence: 99%
“…All the features depicted above lead to the proposed metabolite 6-17␤-dihydroxyandrosta-1,4-dien-3-one. Another evidence is observed on the ESI product ion spectrum of 3-keto-1,4,6-triene steroids (17␣/␤-hydroxy-androsta-1,4,6-triene-3-one), its fragment ions are identical [19] with the fragment ions observed in ESI product ion spectrum of compound 6-17␤-dihydroxyandrosta-1,4-dien-3-one: m/z 159, m/z 171, m/z 173 and m/z 197, suggesting that the water neutral loss from C6 hydroxy group leads to a 3-keto-1,4,6-triene structure identical to the ones mentioned above (Fig. 6).…”
Section: Discussionmentioning
confidence: 88%
“…7). Its ESI fragmentation features are pretty similar to another 3-keto-1,4,6-triene steroids (androsta-1,4,6-triene-3,17-dione) [19]. Due to fragment ions associated with the compound mass and early RT the metabolites 6␣/␤-hydroxyandrosta-1,4-diene-3,17-dione (6␣/␤-hydroxyexemestane) were proposed.…”
Section: Discussionmentioning
confidence: 91%
“…The difficulty seen in the past of obtaining ethical approval for costly in vivo administrations has been overcome with attractive in vitro procedures due to satisfactory correlation factors. [57,58] The in vitro metabolism studies of desoxy-methyltestosterone (DMT), widely known as MADOL, and five of its structural analogues with different substituents at the 17α-position (R═H, ethyl, vinyl, ethynyl and H 3 -methyl) of typical steroid structure was studied in equine liver microsomes and the in vivo metabolism of one of the DMT analogues, desoxy-vinyltestosterone (DVT) using GC-MS in the electron ionization (EI) mode with full-scan acquisition was reported. [59] The detection and metabolic investigation of the novel designer steroid, 3-chloro-17α-methyl-5α-androstan-17β-ol, was performed highlighting its efficiency for doping.…”
Section: Nickelmentioning
confidence: 99%